A tandem organic electroluminescent device

CN114520301BActive Publication Date: 2026-10-27TSINGHUA UNIVERSITY
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202210001683.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-01-04
Publication Date
2026-10-27
Estimated Expiration
2042-01-04

AI Technical Summary

Technical Problem

但这类碱金属或碱土金属类的n型掺杂剂在外电场作用容易向p型掺杂层一侧扩散,进而导致器件在工作中驱动电压上升,器件寿命显著下降,严重地影响了器件的效率和稳定性

Benefits of technology

[0080]采用本发明所述的连接层结构的串联OLED器件兼具驱动电压低、器件效率高、工作寿命长等诸多优势,能够满足当前显示和照明领域的需求。另外,本发明化合物的制备所需各个原材料易得,合成工艺、后处理及提纯过程简易可靠,制备工艺与现行的制备工艺兼容,适用于科学研究及工业生产。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN114520301B_ABST
    Figure CN114520301B_ABST
Patent Text Reader

Abstract

The present application relates to an organic electroluminescent device, belonging to the technical field of photoelectric display devices, and particularly relates to an organic electroluminescent device adopting a specific connecting layer scheme arranged between adjacent light-emitting units in the device to form a series structure. The device comprises an anode, a cathode, at least two electroluminescent units arranged between the anode and the cathode, and a connecting layer arranged between adjacent electroluminescent units, wherein the connecting layer is a multi-layer structure comprising an n-type doped layer, a p-type doped layer and a spacer layer located between the two layers, and the spacer layer is composed of an electron transport material. Since the spacer layer composed of the electron transport material can effectively inhibit the diffusion of the n-type dopant in the n-type doped layer to the p-type doped layer on the other side, the problems of driving voltage rise and device aging caused by the diffusion of the n-type dopant are effectively improved, thereby significantly improving the lifetime and stability of the series organic electroluminescent device.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to an organic electroluminescent device, belonging to the field of optoelectronic display device technology, and specifically to an organic electroluminescent device that forms a series structure by employing a specific connection layer scheme disposed between adjacent light-emitting units in the device. Background Technology

[0002] Organic light-emitting diodes (OLEDs) are a type of organic electroluminescent device, mainly consisting of a cathode, an anode, and a light-emitting unit located between the two electrodes. The light-emitting unit is primarily composed of organic semiconductor materials. As an electro-injection type light-emitting device, when a voltage is applied to the electrodes of an OLED device, holes and anodes are injected into the organic functional layer, while electrons are injected from the cathode into the organic functional layer. Electrons and holes recombine in the light-emitting layer to form excitons, ultimately achieving radiative emission. OLED devices, with their advantages of low power consumption, wide viewing angle, and flexibility, have shown broad application prospects in the fields of solid-state displays and lighting technology.

[0003] In recent years, OLED devices with a tandem structure have attracted widespread attention. The light-emitting principle of tandem OLED devices is similar to that of traditional single-layer OLED devices. The difference lies in that tandem OLED devices consist of multiple light-emitting units connected in series by a connecting layer. This connecting layer acts like an electrode, generating charge carriers in pairs under the drive of an external electric field. These generated charge carriers can be further separated and injected into adjacent light-emitting units. Due to this tandem device structure, each injected electron or hole can generate a photon and achieve radiative emission in each light-emitting unit. Therefore, for a tandem OLED device containing N light-emitting units, its current efficiency is approximately N times that of a single-layer OLED device. To achieve the same brightness, the current density required for tandem OLED devices is significantly reduced, thus helping to improve the efficiency roll-off and lifetime issues of OLED devices.

[0004] Currently, the common interconnect layer structure used in tandem OLED devices is an n-type doped layer / p-type doped layer. The energy level difference between the LUMO level of the n-type doped layer and the HOMO level of the p-type doped layer is small, which can effectively generate charge carriers at a relatively low driving voltage. The dopant in the n-type doped layer is mainly composed of alkali metals or alkaline earth metals with low work function (WF < 3.0 eV), including lithium (Li), sodium (Na), potassium (K), rubidium (Rb), cesium (Cs), magnesium (Mg), and calcium (Ca). However, these alkali metal or alkaline earth metal n-type dopants tend to diffuse towards the p-type doped layer under the influence of an external electric field, which leads to an increase in the driving voltage during device operation, a significant decrease in device lifetime, and seriously affects the efficiency and stability of the device.

[0005] Kodak's patent CN100544020A proposes a series OLED device with an intermediate connector located between adjacent electroluminescent units. The connector includes an n-doped organic layer, a p-doped organic layer, and an interface layer. The interface layer mainly functions to prevent possible interdiffusion between the n-type dopant organic layer and the electron acceptor layer material. This patent emphasizes that the interface layer should be a metal compound or a metal. Specifically, the interface layer can be selected from metals with high work functions, including Ti, Zr, Ti, Nb, Ta, Cr, Mo, W, Re, Fe, Ru, Os, Co, Rh, Ir, Ni, Pd, Pt, Cu, Ag, Au, Zn, Al, In, Sn, or alloys thereof, as well as stoichiometric oxides or non-stoichiometric oxides, stoichiometric sulfides or non-stoichiometric sulfides, stoichiometric tellurides or non-stoichiometric tellurides, stoichiometric nitrides or non-stoichiometric nitrides, stoichiometric carbides or non-stoichiometric carbides. Therefore, the above-mentioned connecting layers are all composed of inorganic materials, the evaporation temperature is generally high, and the thickness needs to be precisely controlled to ensure high transmittance. Summary of the Invention

[0006] Therefore, the purpose of this invention is to provide a novel interconnect layer for tandem OLED devices, addressing the problems existing in the prior art. Specifically, in conventional tandem OLED devices, the interconnect layer is an n-type doped layer / p-type doped layer. During device operation, metallic n-type dopants easily diffuse into the p-type doped layer and the adjacent light-emitting layer, leading to an increase in device driving voltage and a decrease in luminous efficiency.

[0007] A spacer layer structure is introduced between the n-type and p-type doped layers in a tandem OLED device. This spacer layer is composed of nitrogen-containing heterocyclic electron transport materials with good electron transport properties. These materials are all organic semiconductors with low evaporation temperatures and high transmittance in the visible light range. These electron transport materials exhibit strong interactions with metal-based n-type dopants such as alkali metals, alkaline earth metals, and some transition metals. This helps suppress the diffusion of these metal-based n-type dopants into the p-type doped layer, thereby effectively improving the drive voltage rise during device operation and extending the device's lifetime.

[0008] Specifically, the present invention provides a series organic electroluminescent device, comprising the following structure: an anode, a cathode, at least two electroluminescent units disposed between the anode and the cathode, and a connecting layer disposed between adjacent electroluminescent units, wherein each electroluminescent unit comprises at least an electron transport layer and an organic light-emitting layer, characterized in that: the connecting layer is a multi-layer structure, comprising an n-type doped layer, a p-type doped layer and a spacer layer located between the two;

[0009] The p-type doped layer is composed of a p-type dopant host material and a p-type dopant. The p-type dopant host is an organic material with hole transport properties. Specifically, the p-type dopant host material in the p-type doped layer is an organic material with hole transport properties, and can be selected from the following compounds:

[0010]

[0011]

[0012]

[0013] The p-type dopant used in the p-type doped layer is mainly a metal oxide with a high work function, including MoO3, WO3, V2O5, MoO2, and Co3O4, as well as organic semiconductor materials with strong electron-withdrawing ability, including CN6-CP, DDQ, HATCN, and C. 60 F 36 One or a mixture of several of F4TCNQ, F2HCNQ, F6TCNNQ, and TECTFCNBN, with the specific molecular structure of the p-type dopant as follows:

[0014]

[0015] The p-type doped layer is characterized in that the doping ratio of the p-type dopant is from 0.2 wt% to 30 wt%, preferably from 0.5 wt% to 10 wt%.

[0016] The n-type doped layer is composed of an n-type dopant material and an n-type dopant. The n-type dopant material is an organic material with electron transport properties, and the n-type dopant is an alkali metal, an alkaline earth metal, or a transition metal.

[0017] The n-type dopant is an alkali metal, alkaline earth metal, or transition metal; preferably, the n-type dopant is selected from one or a mixture of several of lithium, sodium, potassium, rubidium, cesium, magnesium, calcium, gold, silver, copper, iron, nickel, platinum, palladium, ruthenium, and ytterbium. The most preferred n-type dopant is selected from lithium, silver, and cesium.

[0018] In the aforementioned n-type doped layer, the n-type dopant is an organic material with electron transport properties, specifically selected from the following compounds:

[0019]

[0020]

[0021]

[0022]

[0023] The spacer layer is made of an organic material with electron transport properties, which is different from the n-type doped host material. In this specification, the spacer layer is mainly composed of an electron transport material with good electron transport properties and a nitrogen-containing heterocycle in its molecular structure, which can interact strongly with various metal-based n-type dopants. This type of electron transport material has the structure shown in formula (1):

[0024] R1-Q-R2 Equation (1)

[0025] In formula (1), the bridging group Q is selected from one of the following groups, either substituted or unsubstituted, wherein the substitution in the substituted group Q refers to being replaced by one or a combination of two of the following: deuterium, tritium, cyano, halogen, C1-C10 alkyl, C3-C10 cycloalkyl, silyl, C6-C30 arylamine, C6-C30 aryl, and C2-C30 heteroaryl. This indicates the position where R1 bonds to the bridging group Q. This indicates the position where R2 and the bridging group Q are bonded.

[0026]

[0027]

[0028] R1 and R2 are each independently selected from one of substituted or unsubstituted C3-C60 heteroaryl groups, wherein the heteroaryl group contains at least one nitrogen atom, and the substitution in the substituted heteroaryl group refers to being replaced by one or a combination of two of the following: deuterium, tritium, cyano, halogen, C1-C10 alkyl, C3-C10 cycloalkyl, silyl, C6-C30 aryl, C2-C30 heteroaryl, and the substituent is independently cyclically linked to the connected heteroaryl ring or not cyclically linked.

[0029] Furthermore, R1 and R2 are each independently selected from one of the following groups, either substituted or unsubstituted: pyridinyl, pyrimidinyl, triazine, quinolinyl, isoquinolinyl, quinoxalinyl, quinazolinyl, benzimidazolyl, naphzimidazolyl, o-phenanthrolinel, benzothiazolyl, benzoxazolyl, phenazine, dibenzophenazine, oxadiazolyl, thiadiazolyl, triazolyl, xanthraquinone, anthraquinone. The substitution in R1 and R2 refers to being replaced by one or a combination of two of the following: deuterium, tritium, cyano, halogen, C1-C10 alkyl, C3-C10 cycloalkyl, silyl, C6-C30 aromatic amino, C6-C30 aryl, and C2-C30 heteroaryl. The substituent is independently linked to or not linked to the connected aromatic or heteroaryl ring to form a ring.

[0030] Furthermore, R1 and R2 are each independently selected from one of the following groups, either substituted or unsubstituted:

[0031]

[0032]

[0033]

[0034] Further preferred, in the organic electroluminescent device of the present invention, the electron transport material used as the spacer layer is as shown in formula (1), wherein the bridging group Q in formula (1) is preferably selected from one of the following groups:

[0035]

[0036]

[0037] Continuing with the preferred embodiment, in the organic electroluminescent device of the present invention, the electron transport material used as the spacer layer is as shown in formula (1), wherein R1 and R2 in formula (1) are each independently preferably one of the following groups, either self-substituted or unsubstituted:

[0038]

[0039] Furthermore, among the general formula compounds involved in this invention that can be used to prepare spacer layer materials for tandem OLED devices, the following specific structural compounds are preferred: M1-1 to M1-76, M2-1 to M2-76, M3-1 to M3-76, M4-1 to M4-76, M5-1 to M5-76, M6-1 to M6-76, M7-1 to M7-76, M8-1 to M8-76, M9-1 to M9-76, and M10-1 to M10-76. These compounds are merely representative examples.

[0040]

[0041]

[0042]

[0043]

[0044]

[0045]

[0046]

[0047]

[0048]

[0049]

[0050]

[0051]

[0052]

[0053]

[0054]

[0055]

[0056]

[0057]

[0058]

[0059]

[0060]

[0061]

[0062] Most preferably, in the organic electroluminescent device of the present invention, the organic material with electron transport properties used in the spacer layer is selected from at least one of the following specific compounds:

[0063]

[0064]

[0065]

[0066]

[0067]

[0068]

[0069]

[0070]

[0071]

[0072]

[0073] In this type of tandem organic electroluminescent device of the present invention, the total thickness of the spacer layer is 0.1 nm to 10 nm; more preferably, the total thickness of the spacer layer is 0.3 nm to 5 nm; even more preferably, the total thickness of the spacer layer is 0.5 nm to 1 nm.

[0074] In this type of tandem organic electroluminescent device of the present invention, the number of electroluminescent units is 2 to 6; preferably, the number of electroluminescent units is 2 to 4.

[0075] The tandem organic electroluminescent device of the present invention further includes at least one of a hole injection layer, a hole transport layer, and an electron blocking layer in the light-emitting unit.

[0076] In this specification, the term "substituted or unsubstituted" can refer to a group that replaces one or more substituents. When there are multiple substituents, they can be selected from different substituents. In this invention, the same expression means the same thing, and the range of substituents to be selected is as shown above and will not be repeated here.

[0077] In this specification, "each independently" means that when there are multiple subjects, they may be the same or different from each other.

[0078] Unless otherwise specified in this specification, aryl and heteroaryl groups include both monocyclic and fused-ring types. Monocyclic aryl refers to a molecule containing one or at least two phenyl groups. When the molecule contains at least two phenyl groups, the phenyl groups are independent of each other and connected by single bonds, such as phenyl, diphenyl, and terphenyl. Fused-ring aryl refers to a molecule containing at least two benzene rings, but the benzene rings are not independent of each other; instead, they are fused together by sharing ring edges, such as naphthyl and anthracene. Monocyclic heteroaryl refers to a molecule containing at least one heteroaryl group. When the molecule contains one heteroaryl group and other groups (such as aryl, heteroaryl, alkyl, etc.), the heteroaryl group and other groups are independent of each other and connected by single bonds, such as pyridine, furan, and thiophene. Fused-ring heteroaryl refers to a molecule formed by the fusion of at least one phenyl group and at least one heteroaryl group, or by the fusion of at least two heteroaryl rings, such as quinoline, isoquinoline, benzofuran, dibenzofuran, benzothiophene, and dibenzothiophene.

[0079] The tandem OLED device proposed in this invention employs a novel connecting layer structure, namely, introducing a spacer layer between the n-type doped layer and the p-type doped layer. This spacer layer is composed of a vacuum-deposited electron transport material. This electron transport material has the general structural formula described in formula (1), where the Q group is mainly a π-conjugated group, which can bond the two acceptor groups together, further expanding the conjugated system and improving the transport performance of the spacer layer material, thus facilitating the achievement of a lower driving voltage. R1 and R2 are both electron acceptors, and a typical characteristic of these acceptors is the presence of nitrogen-containing heterocycles in their molecules. The nitrogen atoms in these heterocycles are sp... 2 Hybridization, this type of sp electron with lone pairs 2 Hybridized nitrogen atoms have strong interactions with various metal-based n-type dopants. Therefore, introducing an electron transport material with a general formula (1) structure as a spacer between the n-type and p-type doped layers can effectively suppress the diffusion and migration of metal-based n-type dopants to the p-type doped layer, thereby effectively improving the voltage rise during operation of the tandem organic light-emitting device and enhancing the lifetime and stability of the tandem OLED device.

[0080] The tandem OLED device employing the interconnect layer structure described in this invention possesses numerous advantages, including low driving voltage, high device efficiency, and long operating life, meeting the current demands of the display and lighting fields. Furthermore, the raw materials required for the preparation of the compounds of this invention are readily available, and the synthesis process, post-processing, and purification process are simple and reliable. The preparation process is compatible with existing processes and is suitable for scientific research and industrial production. Attached Figure Description

[0081] Figure 1This is a schematic diagram of the structure of a series organic electroluminescent device having N light-emitting units and N-1 connecting layers, prepared in an embodiment of the organic electroluminescent device of the present invention.

[0082] Figure (1) includes an anode, a cathode, N light-emitting units located between two electrodes, and a connecting layer located between every two adjacent light-emitting units. Each connecting layer has a stacked structure and specifically includes an n-type doped layer, a p-type doped layer, and a spacer layer located between them. Detailed Implementation

[0083] The following section demonstrates and verifies the technical features and advantages of this invention by showcasing the practical application of the connecting layer described in this invention in a tandem organic electroluminescent device and by testing the device's performance.

[0084] A tandem OLED device includes an anode, a cathode, and an organic material layer located between the two electrodes. This organic material layer can be further divided into multiple regions. For example, the organic material layer may include a hole transport region, a light-emitting layer, and an electron transport region.

[0085] In specific embodiments, a substrate can be used below the first electrode or above the second electrode. The substrate is typically made of glass or polymer material with excellent mechanical strength, thermal stability, water resistance, and transparency. Furthermore, thin-film transistors (TFTs) can also be incorporated into the substrate used for displays.

[0086] The first electrode can be formed by sputtering or depositing the material to be used as the first electrode on a substrate. When the first electrode is used as the anode, transparent conductive oxide materials such as indium tin oxide (ITO), indium zinc oxide (IZO), tin dioxide (SnO2), and zinc oxide (ZnO) and any combination thereof can be used. When the first electrode is used as the cathode, metals or alloys such as magnesium (Mg), silver (Ag), aluminum (Al), aluminum-lithium (Al-Li), calcium (Ca), magnesium-indium (Mg-In), and magnesium-silver (Mg-Ag) and any combination thereof can be used.

[0087] Organic material layers can be formed on electrodes using methods such as vacuum thermal evaporation, spin coating, and printing. The compounds used as organic material layers can be small organic molecules, large organic molecules, polymers, and combinations thereof.

[0088] The hole transport region is located between the anode and the light-emitting layer. The hole transport region can be a single-layer hole transport layer (HTL), including a single-layer hole transport layer containing only one compound and a single-layer hole transport layer containing multiple compounds. The hole transport region can also be a multilayer structure including at least one of a hole injection layer (HIL), a hole transport layer (HTL), and an electron blocking layer (EBL).

[0089] The material for the hole transport region can be selected from, but is not limited to, phthalocyanine derivatives such as CuPc, conductive polymers or polymers containing conductive dopants such as polyphenylene ethylene, polyaniline / dodecylbenzenesulfonic acid (Pani / DBSA), poly(3,4-ethylenedioxythiophene) / poly(4-styrenesulfonate) (PEDOT / PSS), polyaniline / camphorsulfonic acid (Pani / CSA), polyaniline / poly(4-styrenesulfonate) (Pani / PSS), aromatic amine derivatives, etc.

[0090] The hole injection layer is located between the anode and the hole transport layer. The hole injection layer can be a single compound material or a combination of multiple compounds.

[0091] The light-emitting layer includes luminescent dyes (i.e., dopants) that can emit different wavelengths of light, and may also include a host material. Depending on the technology, the light-emitting layer material can be different materials such as fluorescent electroluminescent materials, phosphorescent electroluminescent materials, and thermally activated delayed fluorescence materials. In a tandem OLED device, a single light-emitting technology can be used, or a combination of multiple different light-emitting technologies can be used. These different light-emitting materials, classified by technology, can emit light of the same color or different colors of light.

[0092] The OLED organic material layer also includes an electron transport region. The electron transport region can be a single-layer electron transport layer (ETL), i.e., a single-layer electron transport layer containing only one compound or a single-layer electron transport layer containing multiple compounds. Alternatively, the electron transport region can be a multilayer structure including at least one of an electron injection layer (EIL), an electron transport layer (ETL), and a hole blocking layer (HBL).

[0093] In the tandem OLED device described in this invention, each light-emitting unit consists of a hole transport region, a light-emitting layer, and an electron transport region. Multiple light-emitting units are connected in series by a connecting layer. The light-emitting unit can be a monochromatic light-emitting unit that emits a single color such as red, green, or blue, or a monochromatic light-emitting unit that emits different colors such as red, green, and blue, or a single-color light-emitting layer that can emit different colors such as red, green, and blue simultaneously.

[0094] The interconnecting layer in the tandem OLED device of the present invention is shown in Figure (1). The first light-emitting unit is prepared on the anode of the device. The interconnecting layer 1 of the device is prepared between the first light-emitting unit and the second light-emitting unit. The interconnecting layer includes an n-type doped layer, a p-type doped layer and a spacer layer between them. Then, the interconnecting layer 2 and the third light-emitting unit are prepared on the second light-emitting unit. According to the device structure design requirements, N-1 interconnecting layers can be prepared accordingly until the Nth light-emitting unit is prepared. Finally, the cathode of the device is prepared.

[0095] The n-type doped layer mainly consists of a dopant and an n-type dopant. The dopant is primarily an electron transport material, while the n-type dopant is mainly composed of alkali metals, alkaline earth metals, and some transition metals, including one or a mixture of several of lithium (Li), sodium (Na), potassium (K), rubidium (Rb), cesium (Cs), magnesium (Mg), calcium (Ca), gold (Au), silver (Ag), copper (Cu), iron (Fe), nickel (Ni), platinum (Pt), palladium (Pd), ruthenium (Ru), and ytterbium (Yb). In Figure (1), the doping ratio of the metallic n-type dopant in the n-type doped layer is from 0.2 wt% to 30 wt%, with a preferred doping ratio of 0.5 wt% to 10 wt%.

[0096] The p-type doped layer is composed of a p-type dopant material and a p-type dopant. The p-type dopant is an organic material with hole transport properties, and the p-type dopant is a metal oxide with a high work function or an organic semiconductor material with strong electron-withdrawing ability. The p-type dopant may be MoO3, WO3, V2O5, MoO2, Co3O4, CN6-CP, DDQ, HATCN, or C. 60 F 36 One or a mixture of several of F4TCNQ, F4-R-TCNQ, F3-R-TCNQ, F2HCNQ, F6TCNNQ, and TECTFCNBN.

[0097] The spacer layer between the n-type doped layer and the p-type doped layer is mainly composed of electron transport material, with a total thickness of 0.1 nm to 10 nm, more preferably 0.3 nm to 5 nm. The organic material with electron transport properties used in the spacer layer has the structure shown in formula (1).

[0098] R1-Q-R2 (1)

[0099] The fabrication process of the organic electroluminescent device in the embodiments of the present invention is as follows:

[0100] Specifically, the tandem OLED device used in this experiment is a dual-emitting-layer device with a connecting layer. The device fabrication process is as follows: a glass plate coated with an ITO transparent conductive layer is ultrasonically treated in a commercial cleaning agent, rinsed in deionized water, ultrasonically degreased in an acetone:ethanol mixed solvent, baked in a clean environment until all moisture is removed, cleaned with ultraviolet light and ozone, and bombarded with a low-energy cation beam;

[0101] The glass substrate with the anode was placed in a vacuum chamber and evacuated to a vacuum level of 1×10⁻⁶. -5 ~5×10 -4Pa, HATCN is vacuum-deposited as a hole injection layer on the above-mentioned anodic layer film at a deposition rate of 0.05 nm / s and a film thickness of 5 to 10 nm.

[0102] NPB was vacuum-deposited on top of the hole injection layer as the hole transport layer of the device at a deposition rate of 0.1 nm / s and a total film thickness of 30 to 50 nm.

[0103] The light-emitting layer of the device is vacuum-deposited on top of the hole transport layer. The light-emitting layer of this invention includes a host material Be(bq)₂ and a phosphorescent dye Ir(mphmq)₂(tmd). Doping is performed using a multi-source co-evaporation method, with the rate and doping concentration controlled by high and low crystal oscillator probes. The evaporation rate of the host material is adjusted to 0.1 nm / s, and the evaporation rate of the dye in the light-emitting layer is adjusted to 1% to 5% of the host evaporation rate, thereby achieving a predetermined doping ratio. The total film thickness of the light-emitting layer is 20 to 50 nm.

[0104] DPPyA was vacuum-deposited on top of the light-emitting layer as an electron transport layer material at a deposition rate of 0.1 nm / s and a total film thickness of 20 to 60 nm.

[0105] A connection layer with a total thickness of 20 to 60 nm is vacuum-deposited on the electron transport layer (ETL). The n-type doped layer is 10 nm thick, with Bphen as the host material and alkali metals or transition metals such as Li, Cs, and Ag as the n-type dopant, at a doping ratio of 10%. The spacer layer has a thickness of 0 to 10 nm, depending on experimental requirements. The p-type doped layer is 20 nm thick, with NPB as the host material and TECTFCNBN as the p-type dopant, at a doping ratio of 3%.

[0106] Then, NPB of 30nm to 50nm is sequentially evaporated as a hole transport layer, an emissive layer of 20 to 50nm total thickness, an electron transport layer of 20 to 60nm, a 1nm LiF layer as an electron injection layer, and a 150nm Al layer as a cathode. A dual-emissive-layer tandem OLED device is then fabricated.

[0107] Table 1 below shows the organic compounds and their structural formulas used in the tandem OLED devices prepared according to the embodiments of the present invention.

[0108] Table 1:

[0109]

[0110] Device Example 1

[0111] The glass plate coated with the ITO transparent conductive layer was ultrasonically treated in a commercial cleaning agent, rinsed in deionized water, ultrasonically degreased in a acetone:ethanol mixed solvent, baked in a clean environment until all moisture was removed, cleaned with ultraviolet light and ozone, and bombarded with a low-energy cation beam.

[0112] The glass substrate with the anode was placed in a vacuum chamber and evacuated to a vacuum level of 1×10⁻⁶. -5 ~5×10 -4 Pa, HATCN is vacuum-deposited on the above-mentioned anodic layer as a hole injection layer at a deposition rate of 0.05 nm / s and a film thickness of 5 nm.

[0113] NPB was vacuum-deposited on top of the hole injection layer as the hole transport layer of the device at a deposition rate of 0.1 nm / s and a total film thickness of 35 nm.

[0114] The light-emitting layer of the device is vacuum-deposited on top of the hole transport layer. The light-emitting layer of this invention includes the host material Be(bq)₂ and the phosphorescent dye Ir(mphmq)₂(tmd). Doping is performed using a multi-source co-evaporation method, with the rate and doping concentration controlled by high and low crystal oscillator probes. The evaporation rate of the host material is adjusted to 0.1 nm / s, and the evaporation rate of the dye in the light-emitting layer is adjusted to 5% of the host evaporation rate, thereby achieving a predetermined doping ratio. The total film thickness of the light-emitting layer is 24 nm.

[0115] The electron transport layer material DPPyA of the device was vacuum-deposited on top of the light-emitting layer at a deposition rate of 0.1 nm / s and a total film thickness of 40 nm.

[0116] An n-type doped layer was deposited on the electron transport layer (ETL), followed by a 20 nm thick interconnect layer deposited under vacuum. The n-type doped layer was 10 nm thick, with Bphen as the host material and Li as the n-type dopant at a doping ratio of 10%. Then, a 10 nm thick p-type doped layer was deposited, with NPB as the host material and TECTFCNBN as the p-type dopant at a doping ratio of 3%.

[0117] Then, a 50nm NPB layer was sequentially deposited as a hole transport layer, a 24nm thick light-emitting layer with a Be(bq)2:Ir(mphmq)2(tmd) doping ratio of 5%, a 40nm DPPyA layer as an electron transport layer, a 1nm LiF layer as an electron injection layer, and a 150nm Al layer as a cathode. A dual-emitting-layer tandem OLED device was then fabricated.

[0118] It has the following structure:

[0119] ITO / HATCN(5nm) / NPB(35nm) / Be(bq)2:Ir(mphmq)2(tmd)(5%,24nm) / DPPyA(40nm) / Bphen:Li(10%,10nm) / NPB :TECTFCNBN(3%,10nm) / NPB(35nm) / Be(bq)2:Ir(mphmq)2(tmd)(5%,24nm) / DPPyA(40nm) / LiF(1nm) / Al(150nm)

[0120] Device Example 2

[0121] The fabrication method is the same as in Example 1, except that a 0.1 nm L12 spacer layer is introduced between the n-type doped layer and the p-type doped layer. The corresponding tandem OLED device structure is as follows: ITO / HATCN (5 nm) / NPB (35 nm) / Be(bq)2:Ir(mphmq)2(tmd) (5%), 24 nm / DPPyA (40 nm) / Bphen:Li (10%), 10 nm / L12 (0.1 nm) / NPB:TECTFCNBN (3%), 10 nm / NPB (35 nm) / Be(bq)2:Ir(mphmq)2(tmd) (5%), 24 nm / DPPyA (40 nm) / LiF (1 nm) / Al (150 nm)

[0122] Device Example 3: The preparation method is the same as that of Example 2, except that a 0.3 nm L12 spacer layer is introduced between the n-type doped layer and the p-type doped layer.

[0123] Device Example 4: The fabrication method is the same as that of Example 2, except that a 0.5 nm L12 spacer layer is introduced between the n-type doped layer and the p-type doped layer.

[0124] Device Example 5: The preparation method is the same as that of Example 2, except that a 1nm L12 spacer layer is introduced between the n-type doped layer and the p-type doped layer.

[0125] Device Example 6: The fabrication method is the same as that of Example 2, except that a 3nm L12 spacer layer is introduced between the n-type doped layer and the p-type doped layer.

[0126] Device Example 7: The fabrication method is the same as that of Example 2, except that a 5nm L12 spacer layer is introduced between the n-type doped layer and the p-type doped layer.

[0127] Device Example 8: The fabrication method is the same as that of Example 2, except that a 7nm L12 spacer layer is introduced between the n-type doped layer and the p-type doped layer.

[0128] Device Example 9: The fabrication method is the same as that of Example 2, except that a 10 nm L12 spacer layer is introduced between the n-type doped layer and the p-type doped layer.

[0129] Device Example 10

[0130] The preparation method is the same as in Example 1, except that the p-type dopant used is MoO3, the thickness of the p-type doped layer is 10 nm, and the proportion of p-type dopant is 10%. The corresponding tandem OLED device structure is as follows: ITO / HATCN (5 nm) / NPB (35 nm) / Be(bq)2:Ir(mphmq)2(tmd) (5%), 24 nm / DPPyA (40 nm) / Bphen:Li (10%), 10 nm / NPB:MoO3 (10%), 10 nm / NPB (35 nm) / Be(bq)2:Ir(mphmq)2(tmd) (5%), 24 nm / DPPyA (40 nm) / LiF (1 nm) / Al (150 nm).

[0131] Device Example 11: The fabrication method is the same as in Example 10, except that a 0.1 nm L12 spacer layer is introduced between the n-type doped layer and the p-type doped layer. The corresponding tandem OLED device structure is as follows: ITO / HATCN (5 nm) / NPB (35 nm) / Be(bq)2:Ir(mphmq)2(tmd) (5%), 24 nm / DPPyA (40 nm) / Bphen:Li (10%), 10 nm / L12 (0.1 nm) / NPB:MoO3 (10%), 10 nm / NPB (35 nm) / Be(bq)2:Ir(mphmq)2(tmd) (5%), 24 nm / DPPyA (40 nm) / LiF (1 nm) / Al (150 nm)

[0132] Device Example 12: The fabrication method is the same as that of Example 10, except that a 0.3 nm L12 spacer layer is introduced between the n-type doped layer and the p-type doped layer.

[0133] Device Example 13: The fabrication method is the same as that of Example 10, except that a 0.5 nm L12 spacer layer is introduced between the n-type doped layer and the p-type doped layer.

[0134] Device Example 14: The fabrication method is the same as that of Example 10, except that a 1 nm L12 spacer layer is introduced between the n-type doped layer and the p-type doped layer.

[0135] Device Example 15: The fabrication method is the same as that of Example 10, except that a 3nm L12 spacer layer is introduced between the n-type doped layer and the p-type doped layer.

[0136] Device Example 16: The fabrication method is the same as that of Example 10, except that a 5nm L12 spacer layer is introduced between the n-type doped layer and the p-type doped layer.

[0137] Device Example 17: The fabrication method is the same as that of Example 10, except that a 7nm L12 spacer layer is introduced between the n-type doped layer and the p-type doped layer.

[0138] Device Example 18: The fabrication method is the same as that of Example 10, except that a 10 nm L12 spacer layer is introduced between the n-type doped layer and the p-type doped layer.

[0139] The performance summary data of the tandem OLED devices of the present invention, which use L12 as the spacer layer and were fabricated in the above-mentioned device embodiments 1-18, are detailed in Table 2 below.

[0140] Table 2:

[0141]

[0142] Device Example 19

[0143] The preparation method is the same as in Example 1, except that the n-type dopant used is Cs, the thickness of the n-type doped layer is 10 nm, and the proportion of p-type dopant is 10%. The corresponding tandem OLED device structure is as follows: ITO / HATCN (5 nm) / NPB (35 nm) / Be(bq)2:Ir(mphmq)2(tmd) (5%), 24 nm / DPPyA (40 nm) / Bphen:Cs (10%), 10 nm / NPB:TECTFCNBN (3%), 10 nm / NPB (35 nm) / Be(bq)2:Ir(mphmq)2(tmd) (5%), 24 nm / DPPyA (40 nm) / LiF (1 nm) / Al (150 nm)

[0144] Device Example 20: The fabrication method is the same as in Example 19, except that a 0.1 nm L12 spacer layer is introduced between the n-type doped layer and the p-type doped layer. The corresponding tandem OLED device structure is as follows: ITO / HATCN (5 nm) / NPB (35 nm) / Be(bq)2:Ir(mphmq)2(tmd) (5%), 24 nm / DPPyA (40 nm) / Bphen:Cs (10%), 10 nm / L12 (0.1 nm) / NPB:MoO3 (10%), 10 nm / NPB (35 nm) / Be(bq)2:Ir(mphmq)2(tmd) (5%), 24 nm / DPPyA (40 nm) / LiF (1 nm) / Al (150 nm)

[0145] Device Example 21: The fabrication method is the same as that of Example 19, except that a 0.3 nm L12 spacer layer is introduced between the n-type doped layer and the p-type doped layer.

[0146] Device Example 22: The fabrication method is the same as that of Example 19, except that a 0.5 nm L12 spacer layer is introduced between the n-type doped layer and the p-type doped layer.

[0147] Device Example 23: The fabrication method is the same as that of Example 19, except that a 1 nm L12 spacer layer is introduced between the n-type doped layer and the p-type doped layer.

[0148] Device Example 24: The fabrication method is the same as that of Example 19, except that a 3nm L12 spacer layer is introduced between the n-type doped layer and the p-type doped layer.

[0149] Device Example 25: The fabrication method is the same as that of Example 19, except that a 5nm L12 spacer layer is introduced between the n-type doped layer and the p-type doped layer.

[0150] Device Example 26: The fabrication method is the same as that of Example 19, except that a 7nm L12 spacer layer is introduced between the n-type doped layer and the p-type doped layer.

[0151] Device Example 27: The fabrication method is the same as that of Example 19, except that a 10 nm L12 spacer layer is introduced between the n-type doped layer and the p-type doped layer.

[0152] Device Example 28

[0153] The preparation method is the same as in Example 19, except that the p-type dopant used is MoO3, the thickness of the p-type doped layer is 10 nm, and the proportion of p-type dopant is 10%. The corresponding tandem OLED device structure is as follows: ITO / HATCN (5 nm) / NPB (35 nm) / Be(bq)2:Ir(mphmq)2(tmd) (5%), 24 nm / DPPyA (40 nm) / Bphen:Cs (10%), 10 nm / NPB:MoO3 (10%), 10 nm / NPB (35 nm) / Be(bq)2:Ir(mphmq)2(tmd) (5%), 24 nm / DPPyA (40 nm) / LiF (1 nm) / Al (150 nm)

[0154] Device Example 29: The fabrication method is the same as that of Example 31, except that a 0.1 nm L4 spacer layer is introduced between the n-type doped layer and the p-type doped layer. The corresponding tandem OLED device structure is as follows: ITO / HATCN (5 nm) / NPB (35 nm) / Be(bq)2:Ir(mphmq)2(tmd) (5%), 24 nm / DPPyA (40 nm) / Bphen:Cs (10%), 10 nm / L12 (0.1 nm) / NPB:MoO3 (10%), 10 nm / NPB (35 nm) / Be(bq)2:Ir(mphmq)2(tmd) (5%), 24 nm / DPPyA (40 nm) / LiF (1 nm) / Al (150 nm)

[0155] Device Example 30: The fabrication method is the same as that of Example 32, except that a 0.3 nm L12 spacer layer is introduced between the n-type doped layer and the p-type doped layer.

[0156] Device Example 31: The fabrication method is the same as that of Example 32, except that a 0.5 nm L12 spacer layer is introduced between the n-type doped layer and the p-type doped layer.

[0157] Device Example 32: The fabrication method is the same as that of Example 32, except that a 1 nm L12 spacer layer is introduced between the n-type doped layer and the p-type doped layer.

[0158] Device Example 33: The fabrication method is the same as that of Example 32, except that a 3nm L12 spacer layer is introduced between the n-type doped layer and the p-type doped layer.

[0159] Device Example 34: The fabrication method is the same as that of Example 32, except that a 5nm L12 spacer layer is introduced between the n-type doped layer and the p-type doped layer.

[0160] Device Example 35: The fabrication method is the same as that of Example 32, except that a 7nm L12 spacer layer is introduced between the n-type doped layer and the p-type doped layer.

[0161] Device Example 36: The fabrication method is the same as that of Example 32, except that a 10 nm L12 spacer layer is introduced between the n-type doped layer and the p-type doped layer.

[0162] The performance summary data of the tandem OLED devices of the present invention, which use L12 as the spacer layer and were fabricated in the above-mentioned device embodiments 19-36, are detailed in Table 3 below.

[0163] Table 3:

[0164]

[0165] Device Example 37

[0166] The preparation method is the same as in Example 1, except that Ag is used as the n-type dopant, the thickness of the n-type doped layer is 10 nm, and the proportion of p-type dopant is 10%. The corresponding tandem OLED device structure is as follows: ITO / HATCN (5 nm) / NPB (35 nm) / Be(bq)2:Ir(mphmq)2(tmd) (5%), 24 nm / DPPyA (40 nm) / Bphen:Ag (10%), 10 nm / NPB:TECTFCNBN (3%), 10 nm / NPB (35 nm) / Be(bq)2:Ir(mphmq)2(tmd) (5%), 24 nm / DPPyA (40 nm) / LiF (1 nm) / Al (150 nm)

[0167] Device Example 38: The fabrication method is the same as that of Example 41, except that a 0.1 nm L12 spacer layer is introduced between the n-type doped layer and the p-type doped layer. The corresponding tandem OLED device structure is as follows: ITO / HATCN (5 nm) / NPB (35 nm) / Be(bq)2:Ir(mphmq)2(tmd) (5%), 24 nm / DPPyA (40 nm) / Bphen:Ag (10%), 10 nm / L12 (0.1 nm) / NPB:MoO3 (10%), 10 nm / NPB (35 nm) / Be(bq)2:Ir(mphmq)2(tmd) (5%), 24 nm / DPPyA (40 nm) / LiF (1 nm) / Al (150 nm)

[0168] Device Example 39: The fabrication method is the same as that of Example 42, except that a 0.3 nm L12 spacer layer is introduced between the n-type doped layer and the p-type doped layer.

[0169] Device Example 40: The fabrication method is the same as that of Example 42, except that a 0.5 nm L12 spacer layer is introduced between the n-type doped layer and the p-type doped layer.

[0170] Device Example 41: The fabrication method is the same as that of Example 42, except that a 1 nm L12 spacer layer is introduced between the n-type doped layer and the p-type doped layer.

[0171] Device Example 42: The fabrication method is the same as that of Example 42, except that a 3nm L12 spacer layer is introduced between the n-type doped layer and the p-type doped layer.

[0172] Device Example 43: The fabrication method is the same as that of Example 42, except that a 5nm L12 spacer layer is introduced between the n-type doped layer and the p-type doped layer.

[0173] Device Example 44: The fabrication method is the same as that of Example 42, except that a 7nm L12 spacer layer is introduced between the n-type doped layer and the p-type doped layer.

[0174] Device Example 45: The fabrication method is the same as that of Example 42, except that a 10 nm L12 spacer layer is introduced between the n-type doped layer and the p-type doped layer.

[0175] Device Example 46

[0176] The preparation method is the same as in Example 38, except that the p-type dopant used is MoO3, the thickness of the p-type doped layer is 10 nm, and the proportion of p-type dopant is 10%. The corresponding tandem OLED device structure is as follows: ITO / HATCN (5 nm) / NPB (35 nm) / Be(bq)2:Ir(mphmq)2(tmd) (5%), 24 nm / DPPyA (40 nm) / Bphen:Ag (10%), 10 nm / NPB:MoO3 (10%), 10 nm / NPB (35 nm) / Be(bq)2:Ir(mphmq)2(tmd) (5%), 24 nm / DPPyA (40 nm) / LiF (1 nm) / Al (150 nm)

[0177] Device Example 47: The fabrication method is the same as in Example 51, except that a 0.1 nm L12 spacer layer is introduced between the n-type doped layer and the p-type doped layer. The corresponding tandem OLED device structure is as follows:

[0178] ITO / HATCN(5nm) / NPB(35nm) / Be(bq)2:Ir(mphmq)2(tmd)(5%,24nm) / DPPyA(40nm) / Bphen:Cs(10%,10nm) / L12(0.1 nm) / NPB:MoO3(10%,10nm) / NPB(35nm) / Be(bq)2:Ir(mphmq)2(tmd)(5%,24nm) / DPPyA(40nm) / LiF(1nm) / Al(150nm)

[0179] Device Example 48: The fabrication method is the same as that of Example 52, except that a 0.3 nm L12 spacer layer is introduced between the n-type doped layer and the p-type doped layer.

[0180] Device Example 49: The fabrication method is the same as that of Example 52, except that a 0.5 nm L12 spacer layer is introduced between the n-type doped layer and the p-type doped layer.

[0181] Device Example 50: The fabrication method is the same as that of Example 52, except that a 1 nm L12 spacer layer is introduced between the n-type doped layer and the p-type doped layer.

[0182] Device Example 51: The fabrication method is the same as that of Example 52, except that a 3nm L12 spacer layer is introduced between the n-type doped layer and the p-type doped layer.

[0183] Device Example 52: The fabrication method is the same as that of Example 52, except that a 5nm L12 spacer layer is introduced between the n-type doped layer and the p-type doped layer.

[0184] Device Example 53: The fabrication method is the same as that of Example 52, except that a 7nm L12 spacer layer is introduced between the n-type doped layer and the p-type doped layer.

[0185] Device Example 54: The fabrication method is the same as that of Example 52, except that a 10 nm L12 spacer layer is introduced between the n-type doped layer and the p-type doped layer.

[0186] The performance summary data of the tandem OLED devices of the present invention, which use L12 as the spacer layer and were fabricated in the above-mentioned device embodiments 37-54, are detailed in Table 4 below.

[0187] Table 4:

[0188]

[0189]

[0190] Device Example 55: The preparation method is the same as that of Example 1, except that the tandem device has 3 light-emitting units and 2 connecting layers. The corresponding tandem OLED device structure is: ITO / HATCN (5nm) / NPB (35nm) / Be(bq)2:Ir(mphmq)2(tmd) (5%, 24nm) / DPPyA (40nm) / Bphen:Li (10%, 10nm) / NPB:TECTFCNBN (3%, 10nm) / NPB (35nm) / Be(bq)2:Ir(mphmq)2(tmd) (5%, 24nm) / DPPyA (40nm) / Bphen:Li (10%, 10nm) / NPB:TECTFCNBN (3%, 10nm) / NPB (35nm) / Be(bq)2:Ir(mphmq)2(tmd) (5%, 24nm) / DPPyA (40nm) / LiF (1nm) / Al (150nm)

[0191] Device Example 56: The fabrication method is the same as that of Example 55, except that 0.5 nm L12 is introduced as a spacer layer in both connecting layers of this tandem device. The corresponding tandem OLED device structure is: ITO / HATCN (5 nm) / NPB (35 nm) / Be(bq)2:Ir(mphmq)2(tmd) (5%), 24 nm / DPPyA (40 nm) / Bphen:Li (10%), 10 nm / L12 (0.5 nm) / NPB:TECTFCNBN (3%), 10 nm / NPB (35 nm) / Be(bq)2:Ir( mphmq)2(tmd)(5%,24nm) / DPPyA(40nm) / Bphen:Li(10%,10nm) / L12(0.5nm) / NPB:TECTFCNBN(3% ,10nm) / NPB(35nm) / Be(bq)2:Ir(mphmq)2(tmd)(5%,24nm) / DPPyA(40nm) / LiF(1nm) / Al(150nm)

[0192] Device Example 57: The fabrication method is the same as that of Example 55, except that a 1nm L12 layer is introduced as a spacer layer in both connecting layers of this tandem device. The corresponding tandem OLED device structure is: ITO / HATCN (5nm) / NPB (35nm) / Be(bq)2:Ir(mphmq)2(tmd) (5%, 24nm) / DPPyA (40nm) / Bphen:Li (10%, 10nm) / L12 (1nm) / NPB:TECTFCNBN (3%, 10nm) / NPB (35nm) / Be(bq)2:Ir( mphmq)2(tmd)(5%,24nm) / DPPyA(40nm) / Bphen:Li(10%,10nm) / L12(1nm) / NPB:TECTFCNBN(3%, 10nm) / NPB(35nm) / Be(bq)2:Ir(mphmq)2(tmd)(5%,24nm) / DPPyA(40nm) / LiF(1nm) / Al(150nm)

[0193] Device Example 58: The fabrication method is the same as in Example 1, except that this tandem device has 4 light-emitting units and 3 connecting layers. The corresponding tandem OLED device structure is: ITO / HATCN (5nm) / NPB (35nm) / Be(bq)2:Ir(mphmq)2(tmd) (5%), 24nm / DPPyA (40nm) / Bphen:Li (10%), 10nm / NPB:TECTFCNBN (3%), 10nm ... nm) / NPB:TECTFCNBN(3%,10nm) / NPB(35nm) / Be(bq)2:Ir(mphmq)2(tmd)(5%,24nm) / DPPyA(40nm) / Bphen:Li(10%,10n m) / NPB:TECTFCNBN(3%,10nm) / NPB(35nm) / Be(bq)2:Ir(mphmq)2(tmd)(5%,24nm) / DPPyA(40nm) / LiF(1nm) / Al(150nm)

[0194] Device Example 59: The fabrication method is the same as that of Example 58, except that 0.5 nm L12 is introduced as a spacer layer in all three connecting layers of this tandem device. The corresponding tandem OLED device structure is: ITO / HATCN (5 nm) / NPB (35 nm) / Be(bq)2:Ir(mphmq)2(tmd) (5%), 24 nm / DPPyA (40 nm) / Bphen:Li (10%), 10 nm / L12 (0.5 nm) / NPB:TECTFCNBN (3%), 10 nm / NPB (35 nm) / Be(bq)2:Ir(mphmq)2(tmd) (5%), 24 nm / DPPyA (40 nm) / Bphen:Li (10%), 10 nm / L 12(0.5nm) / NPB:TECTFCNBN(3%,10nm) / NPB(35nm) / Be(bq)2:Ir(mphmq)2(tmd)(5%,24nm) / DPPyA(40nm) / Bphen:Li(10%,10nm) / L12(0.5nm) / NPB:TECTFCNBN(3%,10nm) / NPB(35nm) / Be(bq)2:Ir(mphmq)2(tmd)(5%,24nm) / DPPyA(40nm) / LiF(1nm) / Al(150nm)

[0195] Device Example 60: The fabrication method is the same as that of Example 58, except that a 1nm L12 layer is introduced as a spacer layer in all three connecting layers of this tandem device. The corresponding tandem OLED device structure is: ITO / HATCN (5nm) / NPB (35nm) / Be(bq)2:Ir(mphmq)2(tmd) (5%), 24nm / DPPyA (40nm) / Bphen:Li (10%), 10nm / L12 (1nm) / NPB:TECTFCNBN (3%), 10nm / NPB (35nm) / Be(bq)2:Ir(mphmq)2(tmd) (5%), 24nm / DPPyA (40nm) / Bphen:Li (10%), 10nm / L12(1nm) / NPB:TECTFCNBN(3%,10nm) / NPB(35nm) / Be(bq)2:Ir(mphmq)2(tmd)(5%,24nm) / DPPyA(40nm) / Bphen:Li(10%,10nm) / L12(1nm) / NPB:TECTFCNBN(3%,10nm) / NPB(35nm) / Be(bq)2:Ir(mphmq)2(tmd)(5%,24nm) / DPPyA(40nm) / LiF(1nm) / Al(150nm)

[0196] The performance data of the tandem OLED devices of the present invention, which are fabricated in the above-mentioned device embodiments 55-60 and use L12 as the spacer layer and have different numbers of light-emitting units, are summarized in Table 5 below.

[0197] Table 5:

[0198]

[0199] Device Example 61

[0200] The fabrication method is the same as in Example 2, except that a 0.5 nm L1 spacer layer is introduced between the n-type doped layer and the p-type doped layer. The corresponding tandem OLED device structure is as follows: ITO / HATCN (5 nm) / NPB (35 nm) / Be(bq)2:Ir(mphmq)2(tmd) (5%), 24 nm / DPPyA (40 nm) / Bphen:Li (10%), 10 nm / L12 (0.1 nm) / NPB:TECTFCNBN (3%), 10 nm / NPB (35 nm) / Be(bq)2:Ir(mphmq)2(tmd) (5%), 24 nm / DPPyA (40 nm) / LiF (1 nm) / Al (150 nm)

[0201] Device Example 62: The fabrication method is the same as that of Example 2, except that a 1 nm L1 spacer layer is introduced between the n-type doped layer and the p-type doped layer.

[0202] Device Example 63: The fabrication method is the same as that of Example 2, except that a 0.5 nm L2 spacer layer is introduced between the n-type doped layer and the p-type doped layer.

[0203] Device Example 64: The fabrication method is the same as that of Example 2, except that a 1 nm L2 spacer layer is introduced between the n-type doped layer and the p-type doped layer.

[0204] Device Example 65: The fabrication method is the same as that of Example 2, except that a 0.5 nm L3 spacer layer is introduced between the n-type doped layer and the p-type doped layer.

[0205] Device Example 66: The fabrication method is the same as that of Example 2, except that a 1 nm L3 spacer layer is introduced between the n-type doped layer and the p-type doped layer.

[0206] Device Example 67: The fabrication method is the same as that of Example 2, except that a 0.5 nm L4 spacer layer is introduced between the n-type doped layer and the p-type doped layer.

[0207] Device Example 68: The fabrication method is the same as that of Example 2, except that a 1 nm L4 spacer layer is introduced between the n-type doped layer and the p-type doped layer.

[0208] Device Example 69: The fabrication method is the same as that of Example 2, except that a 0.5 nm L5 spacer layer is introduced between the n-type doped layer and the p-type doped layer.

[0209] Device Example 70: The fabrication method is the same as that of Example 2, except that a 1 nm L5 spacer layer is introduced between the n-type doped layer and the p-type doped layer.

[0210] Device Example 71: The fabrication method is the same as that of Example 2, except that a 0.5 nm L6 spacer layer is introduced between the n-type doped layer and the p-type doped layer.

[0211] Device Example 72: The fabrication method is the same as that of Example 2, except that a 1 nm L6 spacer layer is introduced between the n-type doped layer and the p-type doped layer.

[0212] Device Example 73: The fabrication method is the same as that of Example 2, except that a 0.5 nm L7 spacer layer is introduced between the n-type doped layer and the p-type doped layer.

[0213] Device Example 74: The fabrication method is the same as that of Example 2, except that a 1 nm L7 spacer layer is introduced between the n-type doped layer and the p-type doped layer.

[0214] Device Example 75: The fabrication method is the same as that of Example 2, except that a 0.5 nm L8 spacer layer is introduced between the n-type doped layer and the p-type doped layer.

[0215] Device Example 76: The fabrication method is the same as that of Example 2, except that a 1 nm L8 spacer layer is introduced between the n-type doped layer and the p-type doped layer.

[0216] Device Example 77: The fabrication method is the same as that of Example 2, except that a 0.5 nm L11 spacer layer is introduced between the n-type doped layer and the p-type doped layer.

[0217] Device Example 78: The fabrication method is the same as that of Example 2, except that a 1 nm L11 spacer layer is introduced between the n-type doped layer and the p-type doped layer.

[0218] Device Example 79: The fabrication method is the same as that of Example 2, except that a 0.5 nm L13 spacer layer is introduced between the n-type doped layer and the p-type doped layer.

[0219] Device Example 80: The fabrication method is the same as that of Example 2, except that a 1 nm L13 spacer layer is introduced between the n-type doped layer and the p-type doped layer.

[0220] Device Example 81: The fabrication method is the same as that of Example 2, except that a 0.5 nm L14 spacer layer is introduced between the n-type doped layer and the p-type doped layer.

[0221] Device Example 82: The fabrication method is the same as that of Example 2, except that a 1 nm L14 spacer layer is introduced between the n-type doped layer and the p-type doped layer.

[0222] Device Example 83: The fabrication method is the same as that of Example 2, except that a 0.5 nm L19 spacer layer is introduced between the n-type doped layer and the p-type doped layer.

[0223] Device Example 84: The fabrication method is the same as that of Example 2, except that a 1 nm L19 spacer layer is introduced between the n-type doped layer and the p-type doped layer.

[0224] Device Example 85: The fabrication method is the same as that of Example 2, except that a 0.5 nm L20 spacer layer is introduced between the n-type doped layer and the p-type doped layer.

[0225] Device Example 86: The fabrication method is the same as that of Example 2, except that a 1 nm L20 spacer layer is introduced between the n-type doped layer and the p-type doped layer.

[0226] Device Example 87: The fabrication method is the same as that of Example 2, except that a 0.5 nm L21 spacer layer is introduced between the n-type doped layer and the p-type doped layer.

[0227] Device Example 88: The fabrication method is the same as that of Example 2, except that a 1 nm L21 spacer layer is introduced between the n-type doped layer and the p-type doped layer.

[0228] Device Example 89: The fabrication method is the same as that of Example 2, except that a 0.5 nm L22 spacer layer is introduced between the n-type doped layer and the p-type doped layer.

[0229] Device Example 90: The fabrication method is the same as that of Example 2, except that a 1 nm L22 spacer layer is introduced between the n-type doped layer and the p-type doped layer.

[0230] Device Example 91: The fabrication method is the same as that of Example 2, except that a 0.5 nm L25 spacer layer is introduced between the n-type doped layer and the p-type doped layer.

[0231] Device Example 92: The fabrication method is the same as that of Example 2, except that a 1 nm L25 spacer layer is introduced between the n-type doped layer and the p-type doped layer.

[0232] Device Example 93: The fabrication method is the same as that of Example 2, except that a 0.5 nm L26 spacer layer is introduced between the n-type doped layer and the p-type doped layer.

[0233] Device Example 94: The fabrication method is the same as that of Example 2, except that a 1 nm L26 spacer layer is introduced between the n-type doped layer and the p-type doped layer.

[0234] Device Example 95: The fabrication method is the same as that of Example 2, except that a 0.5 nm L27 spacer layer is introduced between the n-type doped layer and the p-type doped layer.

[0235] Device Example 96: The fabrication method is the same as that of Example 2, except that a 1 nm L27 spacer layer is introduced between the n-type doped layer and the p-type doped layer.

[0236] Device Example 97: The fabrication method is the same as that of Example 2, except that a 0.5 nm L28 spacer layer is introduced between the n-type doped layer and the p-type doped layer.

[0237] Device Example 98: The fabrication method is the same as that of Example 2, except that a 1 nm L28 spacer layer is introduced between the n-type doped layer and the p-type doped layer.

[0238] Device Example 99: The fabrication method is the same as that of Example 2, except that a 0.5 nm L29 spacer layer is introduced between the n-type doped layer and the p-type doped layer.

[0239] Device Example 100: The fabrication method is the same as that of Example 2, except that a 1 nm L29 spacer layer is introduced between the n-type doped layer and the p-type doped layer.

[0240] Device Example 101: The fabrication method is the same as that of Example 2, except that a 0.5 nm L31 spacer layer is introduced between the n-type doped layer and the p-type doped layer.

[0241] Device Example 102: The fabrication method is the same as that of Example 2, except that a 1 nm L31 spacer layer is introduced between the n-type doped layer and the p-type doped layer.

[0242] Device Example 103: The fabrication method is the same as that of Example 2, except that a 0.5 nm L32 spacer layer is introduced between the n-type doped layer and the p-type doped layer.

[0243] Device Example 104: The fabrication method is the same as that of Example 2, except that a 1 nm L32 spacer layer is introduced between the n-type doped layer and the p-type doped layer.

[0244] Device Example 105: The fabrication method is the same as that of Example 2, except that a 0.5 nm L33 spacer layer is introduced between the n-type doped layer and the p-type doped layer.

[0245] Device Example 106: The fabrication method is the same as that of Example 2, except that a 1 nm L33 spacer layer is introduced between the n-type doped layer and the p-type doped layer.

[0246] Device Example 107: The fabrication method is the same as that of Example 2, except that a 0.5 nm L35 spacer layer is introduced between the n-type doped layer and the p-type doped layer.

[0247] Device Example 108: The fabrication method is the same as that of Example 2, except that a 1 nm L35 spacer layer is introduced between the n-type doped layer and the p-type doped layer.

[0248] Device Example 109: The fabrication method is the same as that of Example 2, except that a 0.5 nm L37 spacer layer is introduced between the n-type doped layer and the p-type doped layer.

[0249] Device Example 110: The fabrication method is the same as that of Example 2, except that a 1 nm L37 spacer layer is introduced between the n-type doped layer and the p-type doped layer.

[0250] Device Example 111: The fabrication method is the same as that of Example 2, except that a 0.5 nm L43 spacer layer is introduced between the n-type doped layer and the p-type doped layer.

[0251] Device Example 112: The fabrication method is the same as that of Example 2, except that a 1 nm L43 spacer layer is introduced between the n-type doped layer and the p-type doped layer.

[0252] Device Example 113: The fabrication method is the same as that of Example 2, except that a 0.5 nm L49 spacer layer is introduced between the n-type doped layer and the p-type doped layer.

[0253] Device Example 114: The fabrication method is the same as that of Example 2, except that a 1 nm L49 spacer layer is introduced between the n-type doped layer and the p-type doped layer.

[0254] Device Example 115: The fabrication method is the same as that of Example 2, except that a 0.5 nm L57 spacer layer is introduced between the n-type doped layer and the p-type doped layer.

[0255] Device Example 116: The fabrication method is the same as that of Example 2, except that a 1 nm L57 spacer layer is introduced between the n-type doped layer and the p-type doped layer.

[0256] Device Example 117: The fabrication method is the same as that of Example 2, except that a 0.5 nm L75 spacer layer is introduced between the n-type doped layer and the p-type doped layer.

[0257] Device Example 118: The fabrication method is the same as that of Example 2, except that a 1 nm L75 spacer layer is introduced between the n-type doped layer and the p-type doped layer.

[0258] Device Example 119: The fabrication method is the same as that of Example 2, except that a 0.5 nm L79 spacer layer is introduced between the n-type doped layer and the p-type doped layer.

[0259] Device Example 120: The fabrication method is the same as that of Example 2, except that a 1 nm L79 spacer layer is introduced between the n-type doped layer and the p-type doped layer.

[0260] The performance data of the tandem OLED devices of the present invention, which were prepared in the above-mentioned device examples 61-120 and used multiple representative compounds of the present invention as spacers, are summarized in Table 6 below.

[0261] Table 6:

[0262]

[0263]

[0264]

[0265] A comparison of Examples 1 to 9 and Examples 37 to 45 reveals that, with other materials remaining the same in the tandem organic light-emitting diode (OLED) structure, introducing a spacer layer with a thickness of 0.1 nm to 10 nm into the interconnect layer reduces the voltage rise after 24 hours of operation. Simultaneously, the device stability is significantly improved, and the device lifetime is correspondingly increased. It is speculated that during the heating and evaporation process and during device operation, metallic n-type dopants may migrate or diffuse into the p-type dopants and the light-emitting layer, leading to aging of the interconnect layer and exciton quenching in the light-emitting layer, thus reducing device efficiency and lifetime. The optimal thickness for introducing a spacer layer to improve device lifetime is generally approximately 0.1 nm to 10 nm.

[0266] By comparing Examples 1 to 9, Examples 19-27, and Examples 41 to 50, it can be found that the type of n-type dopant has a significant impact on the lifetime of tandem OLED devices. In terms of lifetime alone, the trend is silver > lithium > cesium. This is mainly because, for the same dopant, silver and Bphen have a strong coordination interaction, exhibiting the strongest force. Lithium and cesium primarily interact with Bphen through electrostatic interactions. Since the radius of cesium is much larger than that of lithium, the interaction force between lithium and Bphen is stronger than that between cesium for these two +1 valent ions. Therefore, the order of interaction strength between these three metal n-type dopants and Bphen is silver stronger than lithium, and lithium stronger than cesium. Thus, tandem OLED devices based on silver as an n-type dopant have a longer lifetime than OLED devices based on cesium. Furthermore, since the introduced spacer layer has a certain migration effect on all three metals, the spacer layer described in this invention provides similar lifetime improvement effects for tandem OLED devices using different n-type dopants.

[0267] By comparing Examples 1 to 9 with Examples 10 to 18, Examples 19 to 27 with Examples 28 to 36, Examples 37 to 45 with Examples 46 to 54, it can be found that regardless of whether an organic semiconductor p-type dopant such as TECTFCNBN or an inorganic semiconductor p-type dopant such as MoO3 is used, the spacer layer described in this invention can improve the stability of tandem OLED devices, exhibiting similar effects. This is mainly because the migration and diffusion of metal-based n-type dopants are the main factors leading to lifetime decay and voltage rise during the aging of tandem devices. Therefore, introducing a spacer layer helps to improve the performance of tandem OLED devices using metal-based n-type dopants and different types of p-type dopants.

[0268] In Examples 1, 4, 5, and Examples 61 to 120, nearly 30 different spacer layer materials were used. We found that devices using L12 as the spacer layer performed better than those using L14, specifically in terms of smaller driving voltage variations and longer lifetime. This is presumably because L12 has an outer electron acceptor group of o-phenanthroline, while L4 has an outer electron acceptor group of 2-phenyl-o-phenanthroline. The outer phenyl group not only reduces the electrostatic potential of the nitrogen atom but also introduces steric hindrance, which is detrimental to its interaction with the metal. Therefore, L12 has a stronger ability to block the migration or diffusion of metal-type n-type dopants than L14, resulting in better lifetime for tandem OLED devices using L12 as the spacer layer. Furthermore, it can be observed that Examples 61 to 82 primarily used spacer layer materials containing bis-phenanthroline groups, while Examples 85 to 94 mainly used spacer layer materials containing triazine and pyridine groups. It can be seen that bis-phenanthroline materials in tandem OLED devices are more effective at blocking metal ion migration than materials such as L19 and L20. This may be because the electrostatic potential near the nitrogen atom of the phenanthroline group is larger, resulting in stronger interaction forces with metal-type n-type dopants, thus better suppressing metal diffusion and migration. In addition, Examples 61 to 120 compared the performance of various tandem devices with spacer layer thicknesses of 0.5 nm and 1 nm. The comparison revealed that the tandem OLED device using a 0.5 nm spacer layer had a lower device driving voltage, possibly due to its lower series resistance. However, the tandem OLED device with a 1 nm spacer layer thickness exhibited better lifetime and voltage stability than the tandem OLED device with a 0.5 nm spacer layer thickness. This indicates that using a thicker spacer layer helps to better suppress the diffusion of metal-type n-type dopants, further reflecting the influence of the spacer layer described in this invention on device performance. The spacer layer materials used in Examples 95 to 120 are characterized by having phenylpyridine on one side and an o-phenanthroline group on the other, with bridging groups such as naphthalene, substituted and unsubstituted anthracene, etc. These large π-conjugated groups facilitate the formation of strong π-π stacking to improve electron mobility. Simultaneously, these large π-conjugated bridging groups help expand molecular conjugation, thereby enhancing the stability of negatively charged molecules. Therefore, tandem OLED devices based on such spacer layer materials also exhibit superior stability. Based on the above results, it can be found that the spacer layer constructed from nitrogen-containing heterocyclic electron transport materials has a strong interaction with various metal-based n-type dopants, which helps suppress metal migration or diffusion, thus improving exciton utilization and the efficiency and lifetime of OLED devices.

[0269] Examples 55 to 60 primarily verified the effect of the spacer layer on tandem OLEDs with 3 and 4 light-emitting units, respectively. It can be found that for tandem OLED devices containing 3 and 4 light-emitting units, introducing a 1nm L12 as a spacer layer can also suppress metal migration and diffusion in the n-type doped layer, thereby improving the stability of the organic electroluminescent device.

[0270] In summary, the connection layer design strategy proposed in this invention for novel tandem OLED devices, namely n-type doped layer / spacer layer / p-type doped layer, helps to suppress the diffusion and migration of metal-type n-type dopants in tandem OLED devices, helps to improve the stability of the connection layer and reduce exciton quenching in the light-emitting layer, and can therefore be applied to tandem OLED devices, helping the devices achieve a longer lifetime and lower voltage rise during operation.

[0271] The experimental data above show that the device structure and matching electron transport material described in this invention have excellent performance and significantly improve device performance, and are expected to be promoted for commercial application.

[0272] Although the invention has been described with reference to embodiments, it is not limited to the above embodiments. It should be understood that various modifications and improvements can be made by those skilled in the art under the guidance of the inventive concept, and the appended claims summarize the scope of the invention. Obviously, the above embodiments are merely examples for clear illustration and are not intended to limit the implementation. For those skilled in the art, other variations or modifications can be made based on the above description. It is neither necessary nor possible to exhaustively describe all embodiments here. However, obvious variations or modifications derived therefrom are still within the protection scope of this invention.

Claims

1. A series organic electroluminescent device, comprising the following structure: an anode, a cathode, at least two electroluminescent units disposed between the anode and the cathode, and a connecting layer disposed between adjacent electroluminescent units, wherein each electroluminescent unit includes at least one electron transport layer and an organic light-emitting layer, characterized in that: The connecting layer is a multi-layer structure, including an n-type doped layer, a p-type doped layer, and a spacer layer between them; The n-type doped layer consists of an n-type dopant material and an n-type dopant. The n-type dopant material is an organic material with electron transport properties, and the n-type dopant is an alkali metal, alkaline earth metal, or transition metal. The doping ratio of the n-type dopant is from 0.2 wt% to 30 wt%. The p-type doped layer consists of a p-type dopant material and a p-type dopant. The p-type dopant is an organic material with hole transport properties, and the p-type dopant is a metal oxide with a high work function or an organic semiconductor material with strong electron-withdrawing ability. The doping ratio of the p-type dopant is from 0.2 wt% to 30 wt%. The total thickness of the spacer layer is 0.1 nm to 10 nm; the spacer layer is made of an organic material with electron transport properties, which is different from the n-type doped host material, and the organic material used in the spacer layer has the structure shown in formula (1): (1) In formula (1), the bridging group Q is selected from one of the following groups, either substituted or unsubstituted, wherein the substitution in the substituted group Q refers to being replaced by one or a combination of two of the following: deuterium, tritium, cyano, halogen, C1-C10 alkyl, C3-C10 cycloalkyl, C6-C30 aryl, and C2-C30 heteroaryl. This indicates the position where R1 bonds to the bridging group Q. The positions where R2 and the bridging group Q are bonded: ; In formula (1), R1 and R2 are each independently selected from one of the following groups, either substituted or unsubstituted: ; The substitution in R1 and R2, whether substituted or unsubstituted, refers to being replaced by one or a combination of two selected from halogen, C1~C10 alkyl, C3~C10 cycloalkyl, C6~C30 arylamine, C6~C30 aryl, and C2~C30 heteroaryl.

2. The tandem organic electroluminescent device according to claim 1, characterized in that, The electroluminescent unit includes at least one of a hole injection layer, a hole transport layer, and an electron blocking layer.

3. The tandem organic electroluminescent device according to claim 1, characterized in that, In the n-type doped layer, the doping ratio of the n-type dopant is from 0.5 wt% to 10 wt%. The n-type dopant is selected from one or a mixture of several of lithium, sodium, potassium, rubidium, cesium, magnesium, calcium, gold, silver, copper, iron, nickel, platinum, palladium, ruthenium, and ytterbium.

4. The tandem organic electroluminescent device according to claim 3, characterized in that, The n-type dopant is selected from lithium, silver, or cesium.

5. The tandem organic electroluminescent device according to claim 1 or 3, characterized in that, In the p-type doped layer, the doping ratio of the p-type dopant is from 0.5 wt% to 10 wt%. The p-type dopant is MoO3, WO3, V2O5, MoO2, Co3O4, CN6-CP, DDQ, HATCN, C 60 F 36 One or a mixture of several of F4TCNQ, F2HCNQ, F6TCNNQ, and TECTFCNBN.

6. The tandem organic electroluminescent device according to claim 1, characterized in that, The total thickness of the spacer layer is 0.3 nm to 5 nm.

7. The tandem organic electroluminescent device according to claim 1, characterized in that, The total thickness of the spacer layer is 0.5 nm to 1 nm.

8. The tandem organic electroluminescent device according to claim 1, characterized in that, R1 and R2 are each independently selected from one of the following groups, either substituted or unsubstituted: 。 9. The tandem organic electroluminescent device according to claim 1, characterized in that, The organic material with electron transport properties used in the spacer layer is selected from the following compounds: 。 10. The tandem organic electroluminescent device according to claim 6 or 9, characterized in that, The number of electroluminescent units is 2 to 6.

11. The tandem organic electroluminescent device according to claim 6 or 9, characterized in that, The number of electroluminescent units is 2 to 4.

Citation Information

Patent Citations

  • Tandem OLED having an organic intermediate connector

    CN100544020C

  • Tandem OLED having an organic intermediate connector

    CN101128936A

  • Laminated organic electroluminescent device

    CN106328820A